Growth-Defense Trade-Offs Induced by Long-term Overgrazing Could Act as a Stress Memory - Qu, Kairi; Cheng, Yunxiang; Gao, Kairu; Ren, Weibo; Fry, Ellen L.; Yin, Jingjing; Liu, Yaling (Frontiers in Plant Science, 2022)
Long-term overgrazing is one of the key drivers of global grassland degradation resulting in severe losses of productivity and ecosystem functions, which may result in stress memory, such as a smaller stature of grassland plants. However, the pathways by which the overgrazing-induced stress memory could be regulated by phytohormones are unknown. Here, we investigate the changes of four phytohormones of the cloned offspring of Leymus chinensis that was developed from no-grazing plants (NG) and overgrazing plants (OG) with a grazing history of 30 years. The concentrations of auxin (IAA) and gibberellic acid (GA) in OG plant leaves were 45% and 20% lower than the control, respectively. Meanwhile, the level of abscisic acid (ABA) in OG leaves nearly doubled compared with that in NG leaves. The situation is quite similar in the roots. Unexpectedly, no significant changes in jasmonate acid (JA) levels were observed between OG and NG plants. The changes in the gene expression pattern between OG and NG plants were also investigated by transcriptomic analysis. In total, 302 different expression genes (DEGs) were identified between OG and NG plants which were mainly classified into functions of synthesis, receptor, and signal transduction processes of phytohormones. The expression of 24 key genes related to the biosynthesis and signal transduction of IAA and GA were downregulated in OG plants. Among them, OASA1 and AO1 (regulating the biosynthesis of IAA and ABA, respectively) were significantly reduced by 88% and 92%, respectively. In addition, the content of secondary metabolites related to plant defense, such as flavonoids and phenols, were also increased in leaves. Collectively, the decrease of positive plant growth-related hormones (IAA and GA) together with the increase of plant stress-related hormones, or factors (e.g., ABA, flavonoids, and phenols), induced the growth-defense trade-offs for the adaptation of Leymus chinensis to long-term overgrazing stress. The findings reported here shed new light on the mechanism of plant-animal interaction in grassland ecosystems and provide a deeper insight into optimizing grazing management and sustainable utilization of grasslands.